2020
DOI: 10.1021/acs.analchem.0c03806
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Human Serum Albumin and Sulfur Dioxide in Living Cells Based on a Catalyzed Michael Addition Reaction

Abstract: As vital important bioactive species, human serum albumin (HSA) and sulfur dioxide (SO 2 ) are essential molecules in the organisms and act a pivotal part in many biological events. Although studies have shown that SO 2 -induced HSA radicals can cause oxidative damage, the underlying mechanism of the synergistic effect of HSA and SO 2 in various diseases is obscure, mainly because of the lack of powerful tools that can simultaneously detect HSA and SO 2 in living systems. In this work, we report a novel single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…A class of heme‐peroxidases initiates the one electron oxidation of sulfite to sulfite radical, which enables oxidative damage of biomolecules. Indeed, human serum albumin (HSA), a most abundant plasma protein, has a close biological relationship with (bi)sulfite, enabling the sulfite‐induced HSA radicals formation, resulting in the progression of various diseases states via sulfur metabolism pathway [198] . Interestingly, albumin‐containing metal binding ATCUN motif (amino terminal Cu and Ni binding motif) [199] has no report to the formation of sulfite radical from sulfite, but designed metal‐ATCUN has ability to generate sulfite radical at physiological condition in vitro [200] .…”
Section: Discussionmentioning
confidence: 99%
“…A class of heme‐peroxidases initiates the one electron oxidation of sulfite to sulfite radical, which enables oxidative damage of biomolecules. Indeed, human serum albumin (HSA), a most abundant plasma protein, has a close biological relationship with (bi)sulfite, enabling the sulfite‐induced HSA radicals formation, resulting in the progression of various diseases states via sulfur metabolism pathway [198] . Interestingly, albumin‐containing metal binding ATCUN motif (amino terminal Cu and Ni binding motif) [199] has no report to the formation of sulfite radical from sulfite, but designed metal‐ATCUN has ability to generate sulfite radical at physiological condition in vitro [200] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the amino group of Lys199 in HSA contributes most of the catalytic activity. 7 The results of liang et al showed good performance of this probe molecule for the simultaneous determination of HSA and SO 2 molecules in urine and cells. And this probe was expected to be used in the diagnosis of liver cancer, drug evaluation, and the study of physiological and pathological functions of HSA and SO 2 .…”
Section: Scheme 1 Probe C23mentioning
confidence: 95%
“…Recently Liang et al designed a fluorescent small molecule probe for simultaneous detection of HSA and SO 2 via their distinct fluorescent signals. 7 The design concept was as showed in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cirrhosis also induces abnormality of HSA. , Thus, a combination of two or more different biomarkers would more accurately reflect the progress of hepatic cells given that a single probe for simultaneously detecting dual markers not only is conducive to studying the basic correlation between biomarkers but can also improve the accuracy of diagnostic results. To this end, dual-response or double-locked fluorescent probes have attracted extensive attention for the diagnosis of physiological diseases. Moreover, such a strategy has been already proposed for clinical HCC detection, where an albumin-to-alkaline phosphatase ratio has displayed a close relation with early HCC. A simultaneous detection of HSA and SO 2 has recently been reported for studying the SO 2 -induced HSA radicals, which potentially induces oxidative damage in living cells . It is known that the development of malignant cells would be accompanied with metabolism changes, as reflected by the elevation of lactic acid and glutathione (GSH). , In this regard, a development strategy for monitoring the variation of albumin and GSH is very intriguing.…”
Section: Introductionmentioning
confidence: 99%
“…19 radicals, which potentially induces oxidative damage in living cells. 22 It is known that the development of malignant cells would be accompanied with metabolism changes, as reflected by the elevation of lactic acid and glutathione (GSH). 6,23−25 In this regard, a development strategy for monitoring the variation of albumin and GSH is very intriguing.…”
Section: ■ Introductionmentioning
confidence: 99%